Notas sobre a cidade, a modernidade e os condomínios fechados - Helio Rodrigues de Oliveira Junior (2005)
This paper targets the reasoning on the relations between the city and the spreading of gated communities throughout it. Hence, starting from a reckoning on reality a s a text and the objectivist obsession of modern and scientific realism, this paper seeks to make an outline of some of the consequences for the city s analysis. It seeks also to develop arguments on the way the city is portrayed by a significant part of contemporary social thought and on its implication s towards the understanding of the gated communities spreading processes .Still , it contrasts a few cases in which the gated communities spreading processes are manifested, highlighting their specificities and difficulties which bring about a generalizing rate explanation. Finally, it suggests a pertinence of thinking otherwise the relations between culture and consumption, lifestyles, social conflict and built space, with the intent of understanding the city and the gated communities spreading.